Factors influencing the access to finance of smallholder farmers in Vietnam: A case study of the whole-chain financing in Hanois suburbs - Nguyễn, Trần Hoàng Anh (2020)
This thesis is organized into five chapters: chapter one presents the introduction, which mainly focuses on the background, objectives, and limitation of the study. Chapter two presents a review of relevant study gaps. Chapter three discusses the key terms and methodology used. Chapter four describes the result and discusses the discussion of findings. Chapter five focuses on the solution, policy implications, and conclusion.